Te Vairanga Tuatua o te Te Reo Māori o te Pae Tonga: Cook Islands Māori (Southern dialects) - Nicholas S (http://catalog.paradisec.org.au/repository/SN1, 2012)
Te Vairanga Tuatua o te Te Reo Māori o te Pae Tonga: Collection of language examples in Cook Islands Māori (Southern dialects) is a digital archive of audio visual examples of Cook Islands Māori. It was began in 2012 but has been added to regulalry since then and will continue to be updated and improved. At this time it comprises approximately 120 item sand 100 hours of material constituting by far the largest corpus of Cook Island Māori in existence.